2005
DOI: 10.1128/jb.187.3.923-929.2005
|View full text |Cite
|
Sign up to set email alerts
|

Growth Kinetics of Extremely Halophilic Archaea (Family Halobacteriaceae ) as Revealed by Arrhenius Plots

Abstract: Members of the family Halobacteriaceae in the domain Archaea are obligate extreme halophiles. They occupy a variety of hypersaline environments, and their cellular biochemistry functions in a nearly saturated salty milieu. Despite extensive study, a detailed analysis of their growth kinetics is missing. To remedy this, Arrhenius plots for 14 type species of the family were generated. These organisms had maximum growth temperatures ranging from 49 to 58°C. Nine of the organisms exhibited a single temperature op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
68
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 24 publications
7
68
0
Order By: Relevance
“…It should also be noted that growth at 50°C of the ⌬psmA strain expressing psmA-His 6 (␣1) in trans [GZ130(pJAM204)] was comparable to that of H26, the parent strain of this study (data not shown). Likewise, the Arrhenius plot for cells expressing wild-type ␣1 in this study is in good agreement with that previously published for growth of H. volcanii DS70 (38). It is surprising that such a dramatic increase in overall growth rate, cell yield, and tolerance of stress (low salt and high temperature) was observed for the ␣1 Q2T variant compared to the wild type, since the difference between the two strains expressing these variants at the genetic level is only two nucleotide substitutions in the penultimate codon of the 5Ј end of the psmA gene resulting in a single-amino-acid substitution.…”
supporting
confidence: 81%
“…It should also be noted that growth at 50°C of the ⌬psmA strain expressing psmA-His 6 (␣1) in trans [GZ130(pJAM204)] was comparable to that of H26, the parent strain of this study (data not shown). Likewise, the Arrhenius plot for cells expressing wild-type ␣1 in this study is in good agreement with that previously published for growth of H. volcanii DS70 (38). It is surprising that such a dramatic increase in overall growth rate, cell yield, and tolerance of stress (low salt and high temperature) was observed for the ␣1 Q2T variant compared to the wild type, since the difference between the two strains expressing these variants at the genetic level is only two nucleotide substitutions in the penultimate codon of the 5Ј end of the psmA gene resulting in a single-amino-acid substitution.…”
supporting
confidence: 81%
“…Haloferax volcanii strain DS70 (Wendoloski et al, 2001) was grown with shaking (180 r.p.m.) at 45 uC (Robinson et al, 2005) and cultured in a medium containing (l 21 ) 125 g (2.1 M or 12 %, optimal salinity) or 206 g (3.5 M or 20 %, high, non-optimal salinity) NaCl, 45 g MgCl 2 . 6H 2 O, 10 g MgSO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…To investigate whether UbaA, SAMP, and other SAMP-associated proteins are needed for optimal growth at high temperature, the aerobic growth of H. volcanii parent and single knockout strains was monitored on rich medium at temperatures equal to and above the 42 to 45°C optimum (28). Although all strains grew similar to wild-type at 42°C, ubaA and samp2 mutants were retarded in growth at 50°C (SI Appendix, Fig.…”
Section: Ubaa and Samp2 Are Needed For Optimal Growth At Highmentioning
confidence: 99%